2014
DOI: 10.1126/science.1254610
|View full text |Cite
|
Sign up to set email alerts
|

Loss of avian phylogenetic diversity in neotropical agricultural systems

Abstract: Peer reviewed eScholarship.orgPowered by the California Digital Library University of California of committing a moral act later (Fig. 4). In addition, a moral self-licensing pattern emerged (18), such that committing a moral act earlier in the day was associated with an above-average likelihood of a subsequent immoral act and a decreased likelihood of a subsequent moral act (Fig. 4). Together, the analysis of everyday moral dynamics revealed evidence both for moral contagion through other people's good deeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
222
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(265 citation statements)
references
References 29 publications
22
222
4
2
Order By: Relevance
“…First, the typology could be applied across multiple locations and taxa to elucidate which trends are general and which are context dependent. For example, studies on multiple taxa and from other regions support our observation that agriculture can maintain biodiverse assemblages (22) of rapidly diversifying, but not evolutionary unique, lineages (23). On the other hand, although we found that biodiversity-driven ecosystem processes were largely unresponsive to the land-cover gradient, many regulating services not measured here are likely more dependent on forests.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…First, the typology could be applied across multiple locations and taxa to elucidate which trends are general and which are context dependent. For example, studies on multiple taxa and from other regions support our observation that agriculture can maintain biodiverse assemblages (22) of rapidly diversifying, but not evolutionary unique, lineages (23). On the other hand, although we found that biodiversity-driven ecosystem processes were largely unresponsive to the land-cover gradient, many regulating services not measured here are likely more dependent on forests.…”
Section: Discussionsupporting
confidence: 38%
“…We generated indices for both the evolutionary history and potential of bird assemblages using multiple metrics. Measures of evolutionary history included phylogenetic diversity (PD), Rao's PD, and mean phylogenetic distance, both accounting for and not accounting for species abundances (15,23,34). In calculating these metrics, we took the mean over 500 possible species-level phylogenies (35).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, our models predicting the number of species at a site (α-diversity; Tables S2-S4) coupled with results that describe the kinds of species at a site (β-diversity) support arguments that increasing tree cover around existing forest reserves will lead to small gains in the number of species, but the species gained tend to be rare, unique, and at risk for extinction because of deforestation (2,3,41,42) Our results also suggest that conservation efforts to diversify farmland by increasing tree cover in and around crop fields and pastures leads to large gains in the number of species, but the species gained tend to be common. Our results provide a theoretical basis for aligning conservation strategies to slow extinctions and for boosting some ecosystem services by buffering remaining forests with wildlife-friendly farmland and regenerating forests where politically feasible, given demands to farm the planet (43).…”
Section: Las Crucesmentioning
confidence: 95%
“…1B). These forest elements, together with the agricultural land in which they are embedded, support significant dimensions of biodiversity, whereas the adjacent crop fields and pastures support a different community (2,3).…”
Section: Las Crucesmentioning
confidence: 99%
“…To assess which clades were more similar in WNV response, the number of species with a given WNV response was compared with the means of 10,000 draws of the same number of species from a random pool of remaining species. Families for whom the number of species with a given response was greater than 95% of these draws were considered significantly affiliated with one type of WNV response (38).…”
Section: Methodsmentioning
confidence: 99%